5 reasons why Saturday went kaput - Pappas, Mike (Raton, NM Raton Range, 1988)
Columns written by Mike Pappas, owner of the Sweet Shop Restaurant, for the Raton Daily Range on a wide variety of topics, some historical, some current, some personal.
Newspaper Article by Mike Pappas
Master list item #: 6
File location is in the Raton File Cabinet
Keywords: Saturday; Shopping; Shoppers; Business; Small Town; Raton, New Mexico; Trinidad, Colorado; Pueblos, Colorado; Springer, New Mexico; Maxwell, New Mexico; Clayton, New Mexico; Des Moines, New Mexico